2006
DOI: 10.1016/j.matbio.2005.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between tissue dilatation and differentiation in distraction osteogenesis

Abstract: Mechanical factors modulate the morphogenesis and regeneration of mesenchymally derived tissues via processes mediated by the extracellular matrix (ECM). In distraction osteogenesis, large volumes of new bone are created through discrete applications of tensile displacement across an osteotomy gap. Although many studies have characterized the matrix, cellular and molecular biology of distraction osteogenesis, little is known about relationships between these biological phenomena and the local physical cues gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 58 publications
(55 reference statements)
1
26
0
Order By: Relevance
“…Both models described tissue regeneration in the chamber qualitatively, but more qualitative and quantitative experimental results are necessary to corroborate the predictive capacities of the models. Although these theories predicted some of the main aspects of tissue regeneration in fracture healing, 5,7-9 tissue engineering, 10,11 bone/implant interfaces, 6,12,13 or distraction osteogenesis, [14][15][16][17] they may be criticized for this lack of corroboration.…”
mentioning
confidence: 99%
“…Both models described tissue regeneration in the chamber qualitatively, but more qualitative and quantitative experimental results are necessary to corroborate the predictive capacities of the models. Although these theories predicted some of the main aspects of tissue regeneration in fracture healing, 5,7-9 tissue engineering, 10,11 bone/implant interfaces, 6,12,13 or distraction osteogenesis, [14][15][16][17] they may be criticized for this lack of corroboration.…”
mentioning
confidence: 99%
“…The studies of Carter et al [84] were the first to use finite element models to explore the relationship between local stress/strain distribution and differentiated tissue types, and thus the first to quantify the level of mechanical stimulus. This theory has been used to study fracture healing [84,85] and distraction osteogenesis [86].…”
Section: Models Of Tissue Differentiation Application To Bone Fractumentioning
confidence: 99%
“…Active distraction creates pressure, fl uid fl ow, tensile strain, and tissue dilatation (local deformation occurring equally in all directions) within and around the distraction area. 41,45,46 A computational study has suggested that tissue within the distraction gap experiences a transient increase of pressure and fl uid fl ow for up to 20 min after each distraction cycle and undergoes near-static tensile stretch and tissue dilatation between one distraction cycle and the next. 46 These mechanical stimuli cause changes at the cellular and molecular level and infl uence the proliferation and the differentiation of multipotent mesenchymal cells.…”
Section: Cellular Response To Mechanical Loadingmentioning
confidence: 99%
“…41,45,46 A computational study has suggested that tissue within the distraction gap experiences a transient increase of pressure and fl uid fl ow for up to 20 min after each distraction cycle and undergoes near-static tensile stretch and tissue dilatation between one distraction cycle and the next. 46 These mechanical stimuli cause changes at the cellular and molecular level and infl uence the proliferation and the differentiation of multipotent mesenchymal cells. [17][18][19][20][21][22][23] Studies have demonstrated during the different phases of distraction osteogenesis an increased expression of the various cytokines involved in the regulation of bone synthesis and turnover.…”
Section: Cellular Response To Mechanical Loadingmentioning
confidence: 99%